Microstructural damage dependent stiffness prediction of unidirectional CFRP composite under cyclic loading. (September 2017) - Senthilnathan, K.; Hiremath, Chandrashekhar P.; Naik, N.K.; Guha, Anirban; Tewari, Asim
Abstract: Property degradation for carbon fiber reinforced polymer (CFRP) composites under fatigue is usually modeled by assuming some kind of notional internal damage parameter which keeps growing with fatigue cycles. However, the damage parameter is itself defined as a function of property degradation. Hence, these models do not have a true predictive capability for mechanical property degradation. In this study, controlled microstructural damage was created by subjecting the unidirectional CFRP specimen to tension-tension fatigue load with predetermined stress ratio, load factor and number of cycles. True 3D microstructural damage state, in terms of fiber breakage, matrix microcracking and interface debonding, in CFRP composites was quantitatively measured. The work further mapped the damage state, from 3D damage space, to the stiffness degradation irrespective of how the damage state was achieved. This is for the first time that property degradation in CFRP under cyclic loading was related to the independently measured damage state.